The Rhodesian War fifty years on - Moorcraft, Paul L.; McLaughlin, Peter, 1953- (Pen & Sword Military, 2015)
"Fifty years on, this superb and exciting book depicts the military history of Southern Rhodesia from the first resistance to colonial rule, through the period of UDI by the Smith government to the Lancaster House agreement that transferred power. There are vivid accounts of the operations against the black nationalist 'guerillas' by the security forces and the intensity of the fighting and courage of the participants will surprise and enthrall readers. Atrocities were undoubtedly committed by both sides but equally the protagonists were playing for very high stakes. But this is more than just a book on military operations. The Authors are able to provide expert analysis of the historical situation and examines events up to the present day, including Mugabe's operations against rival tribes and white farmers. For a thorough work on its subject this book cannot be bettered. Essential reading for those wishing to learn more about a counter-insurgency campaign. The ingenuity of the Rhodesian military fighting against overwhelming odds and restricted by sanctions is impressive but the outcome culminating in the Lancaster House Agreement was inevitable."--Publisher description.